Post‐pyloric versus gastric tube feeding for preventing pneumonia and improving nutritional outcomes in critically ill adults - Alkhawaja, Sana (Cochrane Database Syst Rev, 2015)
BACKGROUND: Nutritional support is an essential component of critical care. Malnutrition has been associated with poor outcomes among patients in intensive care units (ICUs). Evidence suggests that in patients with a functional gut, nutrition should be administered through the enteral route. One of the main concerns regarding use of the enteral route is the reduction in gastric motility that is often responsible for limited caloric intake. This increases the risk of aspiration pneumonia as well. Post‐pyloric feeding, in which the feed is delivered directly into the duodenum or the jejunum, could solve these issues and provide additional benefits over routine gastric administration of the feed. OBJECTIVES: To evaluate the effectiveness and safety of post‐pyloric feeding versus gastric feeding for critically ill adults who require enteral tube feeding. SEARCH METHODS: We searched the following databases: Cochrane Central Register of Controlled Trials (CENTRAL;2013 Issue 10), MEDLINE (Ovid) (1950 to October 2013), EMBASE (Ovid) (1980 to October 2013) and the Cumulative Index to Nursing and Allied Health Literature (CINAHL) via EBSCO host (1982 to October 2013). We reran the search on 4 February 2015 and will deal with the one study of interest when we update the review. SELECTION CRITERIA: Randomized or quasi‐randomized controlled trials comparing post‐pyloric versus gastric tube feeding in critically ill adults. DATA COLLECTION AND ANALYSIS: We extracted data using the standard methods of the Cochrane Anaesthesia, Critical and Emergency Care Group and separately evaluated trial quality and data extraction as performed by each review author. We contacted trials authors to request missing data. MAIN RESULTS: We pooled data from 14 trials of 1109 participants in a meta‐analysis. Moderate quality evidence suggests that post‐pyloric feeding is associated with low rates of pneumonia compared with gastric tube feeding (risk ratio (RR) 0.65, 95% confidence interval (CI) 0.51 to 0.84). Low‐quality evidence shows an increase in the percentage of total nutrient delivered to the patient by post‐pyloric feeding (mean difference (MD) 7.8%, 95% CI 1.43 to 14.18). Evidence of moderate quality revealed no differences in duration of mechanical ventilation or in mortality. Intensive care unit (ICU) length of stay was similar between the two groups. The effect on the time required to achieve the full nutrition target was uncertain (MD ‐1.99 hours 95% CI ‐10.97 to 6.99) (very low‐quality evidence). We found no evidence suggesting an increase in the rate of complications during insertion or maintenance of the tube in the post‐pyloric group (RR 0.51, 95% CI 0.19 to 1.364; RR1.63, 95% CI 0.93 to 2.86, respectively); evidence was assessed as being of low quality for both. Risk of bias was generally low in most studies, and review authors expressed concern regarding lack of blinding of the caregiver in most trials. AUTHORS' CONCLUSIONS: We found moderate‐quality evidence of a 30% lower rate of pneumonia associated with post‐pyloric feeding and low‐quality evidence suggesting an increase in the amount of nutrition delivered to these participants. We do not have sufficient evidence to show that other clinically important outcomes such as duration of mechanical ventilation, mortality and length of stay were affected by the site of tube feeding. Low‐quality evidence suggests that insertion of a post‐pyloric feeding tube appears to be safe and was not associated with increased complications when compared with gastric tube insertion. Placement of the post‐pyloric tube can present challenges; the procedure is technically difficult, requiring expertise and sophisticated radiological or endoscopic assistance. We recommend that use of a post‐pyloric feeding tube may be preferred for ICU patients for whom placement of the post‐pyloric feeding tube is feasible. Findings of this review preclude recommendations regarding the best method for placing the post‐pyloric feeding tube. The clinician is left with this decision, which should be based on the policies of institutional facilities and should be made on a case‐by‐case basis. Protocols and training for bedside placement by physicians or nurses should be evaluated.